2017
DOI: 10.17957/tpmj/17.3857
|View full text |Cite
|
Sign up to set email alerts
|

Molar Caries; Distal Surface Mandibular Second Molar Caries, Existence and Association With Partially Erupted Mandibular Third Molar

Abstract: ABSTRACT… Objectives:To identify risk factor of distal surface caries on mandibular second molar associated with partially erupted mandibular third molar. Setting: The study was conducted in the Department of Oral and Maxillofacial Surgery, Liaquat University Hospital Jamshoro/Hyderabad from April 2013 to September2013. Methodology: Total 273 patients of either gender with age 16-45 years had partially impacted mandibular third molar, were included. Diagnosis was made on clinical as well as periapical view and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…The common reasons for presenting third molar impaction removal in this age range was pain, swelling, trismus because of pericoronitis and dental caries. The mean age was 27.2±6.177 years, and the 3 rd decade is the dominant age group, like other studies 6,22 . It has been reported that during removal of impaction, patient's age is an important factor because many studies have reported that postoperative complications are increased in older patients.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The common reasons for presenting third molar impaction removal in this age range was pain, swelling, trismus because of pericoronitis and dental caries. The mean age was 27.2±6.177 years, and the 3 rd decade is the dominant age group, like other studies 6,22 . It has been reported that during removal of impaction, patient's age is an important factor because many studies have reported that postoperative complications are increased in older patients.…”
Section: Discussionsupporting
confidence: 76%
“…Increase in duration of surgery chances of experiencing pain (VAS>1) 23 . Some studies showed, impaction of lower 3 rd molar was more common in males than females 6,21,24 however as many studies showed female predilection in patients with impacted lower 3 rd molar 22,25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Maxillofacial surgeons routinely carry out minor oral surgical procedures, the removal of wisdom is also one of them. 2,3 "Ninety percent of people have at least one impacted wisdom tooth". 4 Most mandibular third molar extractions are carried out without intra-or post-operative difficulties, but sometimes severe complications may also occur, like pain, trismus, dry socket, infection, hemorrhage, sensory nerve damage (Inferior Alveolar Nerve, Lingual Nerve), and damage to adjacent second molar".…”
Section: Introductionmentioning
confidence: 99%
“…4 Most mandibular third molar extractions are carried out without intra-or post-operative difficulties, but sometimes severe complications may also occur, like pain, trismus, dry socket, infection, hemorrhage, sensory nerve damage (Inferior Alveolar Nerve, Lingual Nerve), and damage to adjacent second molar". 2,4,5 Before procedure radiographic evaluation has been considered as an important factor to predict possible IAN (Inferior Alveolar Nerve) injury during surgery. 6 Orthopentogram (OPG) and periapicalx-rays are complementary radiographs taken before procedure for evaluation of degree of surgical difficulty, third molar morphology and position, operative risk and proximity to adjacent vital structures, such as Inferior Alveolar Nerve.…”
Section: Introductionmentioning
confidence: 99%